International Students’ Cross-Cultural Adjustment: Determining Predictors of Cultural Intelligence - Kay Tze Hong; Siew Imm Ng; Pei San Lai (Universitas Djuanda, 2021)
Globalization have made intercultural competencies crucial for working and interacting effectively with people from diverse nationality, ethnics, and racial groups. Thus, this study tends to examine the predictors of cultural intelligence among international students and to propose strategies that could help international students to better adjust themselves while studying in Malaysia. A quantitative research approach was used in this study. Questionnaires were distributed and a sample size of the study collected consisted of 194 international students. Structural Equation Model using SMARTPLS was implemented to achieve the objectives of this study. The findings found that “Openness to Experience” personality trait, mainstream social connectedness, cultural exposure, and cross-cultural training were found to be positively related to cultural intelligence. Furthermore, cultural intelligence was found to have a positive significant relationship with cross-cultural adjustment. These findings underline the importance of predictors and cultural intelligence in understanding successful international students’ cross-cultural adjustments. The study also examines cultural intelligence in a multiple loci of intelligences framework, which consists of capabilities such as motivational, mental and behavioral aspects. This study has contributed to the area of cultural intelligence and cross-cultural adjustments by providing suggestions to industry players such as the Higher Education Institution, government agencies and managers in enhancing cultural intelligence of international students or expatriates.